Impact of an Abdominal Compression Bandage on the Completion of Colonoscopy for Obese Adults: A Prospective Randomized Controlled Trial - Ting-Ting Liu; Yi-Teng Meng; Feng Xiong; Cheng Wei; Su Luo; Sheng-Gang Zhan; Yang Song; Ying-Xue Li; Rui-Yue Shi; Jun Yao; Li-Sheng Wang; De-Feng Li (Canadian Journal of Gastroenterology and Hepatology)
Background and Aim. Obesity has been linked to incomplete colonoscopy. In the present study, we aimed to determine whether an abdominal compression bandage could improve the complete colonoscopy rate (CCR) of obese patients. Methods. Eligible patients were randomly allocated into the abdominal bandage and conventional groups during a routine colonoscopy. The primary outcome was CCR. Results. A total of 250 eligible patients were randomly assigned to the abdominal bandage and conventional groups from January 2021 to April 2021. Eleven patients (five in the abdominal bandage group and six in the conventional group) were excluded due to schedule cancellation after randomization, and 239 patients were eventually included in the final analysis. There were no significant differences between the two groups regarding baseline characteristics (P > 0.05). Furthermore, no significant differences were observed in terms of advanced adenoma detection rate (AADR), polyp detection rate (PDR), bowel preparation scale (BBPS), bubble scale (BS), and withdrawal time between the two groups (P > 0.05). However, compared with the conventional group, the cecal insertion time (CIT) of the abdominal bandage group was significantly shortened (279.00 (234.50–305.75) vs. 421.00 (327.00–485.00), P < 0.001), and the CCR (96.7% vs. 88.2%, P = 0.01) and adenoma detection rate (ADR) (47.5% vs. 32.8%, P < 0.001) were improved. Besides, logistic regression analysis showed that body mass index (BMI) and abdominal compression bandage were associated with CCR. Conclusions. Abdominal compression bandages could effectively shorten CIT and improve CCR and ADR for obese patients during a routine colonoscopy. This trial is registered with the Chinese Clinical Trial Registry (No. ChiCTR2100043556).